The Impact of Cognitive Strategies and Graphic Organizers on Kurdish EFL Learners’ Language Ego - Padar, Hunar Omer Mohammad Amin; Nabifar, Nesa; Mirzapour, Fatemeh (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The current research sought to explore the impact of cognitive strategies and graphic organizers on Kurdish EFL learners’ language ego. Methods and Materials: One hundred Kurdish EFL learners from a state university in Iraq's Kurdistan Region participated in this quasi-experimental research. The students were EFL learners in the TEFL field and belonged to two faculties. The learners were between the ages of 18 and 22. There were both males and females, after homogenizing them with the Oxford Placement Test (OPT), a sample of ninety-nine participants from the study were chosen. The study sample was split into three groups: the experimental group on cognitive strategy, the graphic organizer group, and the control group. Each class had 33 learners. Two instruments were used to collect data: the Oxford placement test and the language ego questionnaire as well as pretest and the posttest. They had thirteen sessions of treatment. Results: Data analysis revealed that both cognitive strategies and graph organizers positively impacted the writing skills of English as a Foreign Language (EFL) learners. However, the group receiving graphic organizer treatment outperformed in its effect on learners' writing performance, and positively impacted learners' perceptions of their writing abilities and contribute to an improvement in language ego. Conclusion: The current research findings could assist creators of textbooks, educational organizers, materials developers, language institutions, educators, and students create a more effective environment for learning foreign languages and enhancing writing skills.